Mean field variational Bayesian inference for nonparametric regression with measurement error - Pham, Tung H.; Ormerod, John T.; Wand, M.P. (Computational statistics & data analysis, 2013)
A fast mean field variational Bayes (MFVB) approach to nonparametric regression when the predictors are subject to classical measurement error is investigated. It is shown that the use of such technology to the measurement error setting achieves reasonable accuracy. In tandem with the methodological development, a customized Markov chain Monte Carlo method is developed to facilitate the evaluation of accuracy of the MFVB method.